2016
DOI: 10.14805/jphchem.2016.art52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant, Antimicrobial and Anticancer activity of Thiazole Tagged Isatin Hydrazones

Abstract: Isatin and its derivatives is versatile lead molecule for potential bioactive agents and shows wide spectrum of activities. In this study, we evaluated antioxidant, antimicrobial and cytotoxic activity of isatin-3-[N2-(2-benzalaminothiazol-4-yl)] hydrazone derivatives using well defined models. Antioxidant activity of the isatin derivatives (Va-Vj) was evaluated by using the 1, 1-diphenyl-2-picryl hydrazine radicals scavenging assay. The antimicrobial activity is evaluated by cup plate method and anticancer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
2
4
0
1
Order By: Relevance
“…Moreover, all the rats survived throughout the study. This result was corroborated with the previous studies [ 32 , 33 ] in which no severe signs of toxicity and mortality were identified due to the treatment of A. muricata leaf ethanol extract. Furthermore, the weight recorded every two days manifested no significant difference, but the weight of the rats began increasing towards the end of study.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, all the rats survived throughout the study. This result was corroborated with the previous studies [ 32 , 33 ] in which no severe signs of toxicity and mortality were identified due to the treatment of A. muricata leaf ethanol extract. Furthermore, the weight recorded every two days manifested no significant difference, but the weight of the rats began increasing towards the end of study.…”
Section: Discussionsupporting
confidence: 91%
“…The isatin–hydrazone/hydrazide hybrids possess considerable anticancer activity and compound 11 (IC 50 : 6.3–10.8 μM, MTT assay) was comparable to doxorubicin (IC 50 : 6.1–7.6 μM) against HepG2, A549, and MCF‐7 cancer cell lines, whereas hybrids 12 (IC 50 : 2.90–7.61 μM, MTT assay) were 4.2–17.6‐fold more potent than 5‐fluorouracil (IC 50 : 32.15 and 51.16 μM) against HepG2 and Jurkat cancer cell lines. [ 48–50 ] Moreover, hybrids 12a,b (IC 50 : >100 μM) were nontoxic towards normal HEK‐293 cells and SI > 13.1. Thus, both of them could act as hit compounds for the development of novel anticancer chemotherapeutic agents.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%
“…Numerous thiazole derivatives have been synthesized and introduced as antimicrobial [12][13][14], anticonvulsant [15,16], anticancer [17,18], and antidiabetic agents [19,20]. Synthetic thiazoles with antioxidant capacity [21][22][23] or with two or more biological properties, for example, antioxidant, antimicrobial, and anticancer [24], antitumor, antioxidant, and antimicrobial [25], antibacterial, antifungal, and anti-HIV [26], were available.…”
Section: Introductionmentioning
confidence: 99%